Polysubstance use poisoning deaths in Canada: an analysis of trends from 2014 to 2017 using mortality data - Sarah Konefal; Adam Sherk; Bridget Maloney-Hall; Matthew Young; Pam Kent; Emily Biggar (BMC, 2022)
Abstract Background Over the past decade, rates of drug poisoning deaths have increased dramatically in Canada. Current evidence suggests that the non-medical use of synthetic opioids, stimulants and patterns of polysubstance use are major factors contributing to this increase. Methods Counts of substance poisoning deaths involving alcohol, opioids, other central nervous system (CNS) depressants, cocaine, and CNS stimulants excluding cocaine, were acquired from the Canadian Vital Statistics Death Database (CVSD) for the years 2014 to 2017. We used joinpoint regression analysis and the Cochrane-Armitage trend test for proportions to examine changes over time in crude mortality rates and proportions of poisoning deaths involving more than one substance. Results Between 2014 and 2017, the rate of substance poisoning deaths in Canada almost doubled from 6.4 to 11.5 deaths per 100,000 population (Average Annual Percent Change, AAPC: 23%, p < 0.05). Our analysis shows this was due to increased unintentional poisoning deaths (AAPC: 26.6%, p < 0.05) and polysubstance deaths (AAPC: 23.0%, p < 0.05). The proportion of unintentional poisoning deaths involving polysubstance use increased significantly from 38% to 58% among males (p < 0.0001) and 40% to 55% among females (p < 0.0001). Polysubstance use poisonings involving opioids and CNS stimulants (excluding cocaine) increased substantially during the study period (males AAPC: 133.1%, p < 0.01; females AAPC: 118.1%, p < 0.05). Conclusions Increases in substance-related poisoning deaths between 2014 and 2017 were associated with polysubstance use. Increased co-use of stimulants with opioids is a key factor contributing to the epidemic of opioid deaths in Canada.